A strain model for fatigue‐loaded concrete. (26th July 2017) - von der Haar, Christoph; Marx, Steffen
Abstract : In this contribution, an additive strain model is used to describe the deformation behavior of concrete. The model assumes that elastic, viscous, thermal, and damage‐induced strains occur in concrete. The strain components develop independently of each other as a function of the number of load cycles, test duration, and characteristic parameters of the stress cycles. The focus of this paper is on the determination of a creep‐relevant stress level to estimate the magnitude of the viscous deformation component as a function of the fatigue stress. Experimentally measured strains of fatigue‐loaded concrete specimens are divided into the strain components assumed by the additive strain model and analyzed. The investigations yield new insights into the strain and material behavior of fatigue‐loaded concrete.